1998
DOI: 10.1177/096032719801700603
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cadmium as indicator of renal cadmium in humans: an autopsy study

Abstract: Objective: To estimate the equivalent cadmium levels in renal cortex and in urine, as based on autopsy analysis of subjects not exposed to cadmium occupationally. Methods: The levels of Cd were determined in renal cortex, liver, urine and urinary bladder of 39 subjects deceased at the age 42+14 years. Flame atomic absorption spectrometry (kidneys, liver) and flameless AAS (urine, bladder) were used. Results: The urinary cadmium level determined post mortem is strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
1
16
0
2
Order By: Relevance
“…Nilsson et al (2000) found no significant association between U-Cd and K-Cd as determined by an X-ray fluorescence technique in a group of Swedish farmers. Orlowski et al (1998) found a significant association, but this was in an autopsy study using urine samples contaminated with Cd from bladder autolysis.…”
Section: Introductionmentioning
confidence: 86%
“…Nilsson et al (2000) found no significant association between U-Cd and K-Cd as determined by an X-ray fluorescence technique in a group of Swedish farmers. Orlowski et al (1998) found a significant association, but this was in an autopsy study using urine samples contaminated with Cd from bladder autolysis.…”
Section: Introductionmentioning
confidence: 86%
“…The urinary creatinine corrected Cd concentration – a well recognized surrogate marker for Cd exposure (Amzal et al, 2009; Choudhury et al, 2001; Jarup et al, 1998; Orlowski et al, 1998) – was defined as the exposure variable. Urinary creatinine corrected Cd was expressed as μg Cd/g creatinine.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements included cadmium in blood as a measure mainly of ongoing exposure (expected to be fairly constant over time) and urine as a measure of body burden (cadmium in urine correlates well with cadmium in the kidney cortex; Järup et al 1998; Orlowski et al 1998). To control for possible confounding/effect modification, we also determined lead in blood (Lin et al 2003).…”
Section: Methodsmentioning
confidence: 99%